Z papieru do sieci - sposoby funkcjonowania czasopism hobbystycznych w przestrzeni Internetu - Lubczyńska, Aleksandra (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The development of new technologies, including the Internet, has a huge impact on modern communication. In the near future, new communication channels may dominate the existing ones. This is also reflected in the offer of publishing houses and media companies. The progressive fragmentation of audiences is evidenced by the growing figures for thematic channels on television, the increased number of users of narrowly profiled websites and the developing readership of specialist newspapers, coupled with a decrease in interest in general press. All of this made the publishers aware that in order to increase the reach of their products and get to the widest possible group of users, they must take action aimed at diversification, i.e., expanding to a new level of communication. In this context, the aim of the article is to identify the typology of the most characteristic manner in which hobby magazines function on the Internet. Another goal is to verify the thesis that, as is the case with other segments of the Polish press, hobby magazines are also migrating to virtual reality. Taking advantage of the development of the Internet and strengthened media market, they may decide to colonise it. Using the method of media content analysis, 73 hobby magazines were examined and 5 ways of their functioning on the web were distinguished.